STRATEGI PENGEMBANGAN WISATA BERBASIS ECOTOURISM DI AGROWISATA KEBUN TEH JAMUS KABUPATEN NGAWI - Lilian Rahma Normalitha; Aufarul Marom; Herbasuki Nurcahyanto (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Jamus Tea Garden Agrotourism is one of the tourist destinations that rely on beautiful natural panoramas located in Ngawi Regency, East Java. In addition, it is also part of the tourist attraction of the Girikerto Tourism Village. However, the management and development of Jamus Tea Garden Agrotourism until now still cannot be said to be optimal. The problem faced is the lack of maintenance of infrastructure and facilities and the absence of efforts to develop the attraction owned. This results in a decrease in the number of tourist visits almost every year. This study aims to analyze the internal and external environmental conditions of Jamus Tea Garden Agrotourism and formulate an ecotourism-based tourism development strategy at Jamus Tea Garden Agrotourism. This research uses the theory of strategic planning by John. M. Bryson descriptive qualitative research method with SWOT analysis technique and tested using Litmus Test to be able to formulate the right strategy. The results of this study indicate that Jamus Tea Garden Agritourism in management and tourism development efforts have not run optimally so that the right strategy is needed to overcome these problems. The results of the SWOT analysis found 10 strategic issues and then conducted a litmus test obtained 7 issues that are strategic, with 3 issues that have the highest score, namely Utilizing beautiful plantation areas for ecotourism development efforts, Utilizing the attractiveness of tea plantations as educational tours by creating tour packages for the Girikerto Tourism Village and Collaborating with investors to be able to increase the funding budget for tourism development.